2018
DOI: 10.1007/s00424-018-2125-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium mishandling impairs contraction in right ventricular hypertrophy prior to overt heart failure

Abstract: Currently, there are no tailored therapies available for the treatment of right ventricular (RV) hypertrophy, and the cellular mechanisms that underlie the disease are poorly understood. We investigated the cellular changes that occur early in the progression of the disease, when RV hypertrophy is evident, but prior to the onset of heart failure. Intracellular Ca ([Ca]) handling was examined in a rat model of monocrotaline (MCT)-induced pulmonary hypertension and subsequent RV hypertrophy. [Ca] and stress prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…The slopes of the isometric heat-stress relations for the control and isoproterenol cases were the same despite an increase in force in the isoproterenol case (Figure 5B). This suggests that isoproterenol has no direct effect on the chemo-mechanical energy transduction of cardiac myofilaments and that the augmentation of contractility arises indirectly from an increase in the peak of the cytosolic Ca 2+ transient (Tamura et al, 1992;Kassiri et al, 2000;Power et al, 2018). Our measurement of a null effect of isoproterenol on economy, but a higher activation heat in the presence of isoproterenol, is consistent with earlier observations reported in the literature (Gibbs, 1967;Gibbs and Gibson, 1972;Barclay et al, 1979).…”
Section: Implications For Economy Of Contractionsupporting
confidence: 91%
See 2 more Smart Citations
“…The slopes of the isometric heat-stress relations for the control and isoproterenol cases were the same despite an increase in force in the isoproterenol case (Figure 5B). This suggests that isoproterenol has no direct effect on the chemo-mechanical energy transduction of cardiac myofilaments and that the augmentation of contractility arises indirectly from an increase in the peak of the cytosolic Ca 2+ transient (Tamura et al, 1992;Kassiri et al, 2000;Power et al, 2018). Our measurement of a null effect of isoproterenol on economy, but a higher activation heat in the presence of isoproterenol, is consistent with earlier observations reported in the literature (Gibbs, 1967;Gibbs and Gibson, 1972;Barclay et al, 1979).…”
Section: Implications For Economy Of Contractionsupporting
confidence: 91%
“…The isoproterenol dose-response curve for active force development saturates at concentrations above 0.1 µmol l −1 (Monasky et al, 2008). We chose a concentration of 0.5 µmol l −1 to ensure that the maximum inotropic response is elicited, which is within the typical range, 0.1 µmol l −1 (Barclay et al, 1979) to 1 µmol l −1 (Power et al, 2018), used for cardiac muscle experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…β2-adrenergic receptors are restricted to the t-tubule SL in ventricular tissue (Schobesberger et al, 2017), and can produce the same effects as β1-adrenergic receptors, although they can couple to both stimulatory and inhibitory G protein coupled receptors (Triposkiadis et al, 2009). We have previously shown that loss of t-tubules in right ventricle hypertrophy coincides with an attenuated inotropic response to β-adrenergic stimulation (Power et al, 2018). However, the results from this study suggest that detubulation per se does not explain the impaired β-adrenergic responsiveness observed in heart failure.…”
Section: ß-Adrenergic Activation Of the Detubulated Myocardiummentioning
confidence: 99%
“…Disruption and/or loss of myocyte t-tubule structure has been reported in myocytes from human (Crossman et al, 2011) and many animal models (Wei et al, 2010;Ward and Crossman, 2014;Power et al, 2018) of heart disease in which contraction is compromised. The resulting increased t-tubule heterogeneity has been suggested as causing prolonged action potential duration (Beuckelmann et al, 1993;Tomaselli and Marban, 1999), asynchrony of subcellular Ca 2+ release, and reduced force in diseased myocytes (Heinzel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%